2022
DOI: 10.1186/s40359-022-00749-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing meaningful work among Hungarian employees: testing psychometric properties of work and meaning inventory in employee subgroups

Abstract: Background The construct of meaningful work (MW) has become the subject of various studies. Workers who experience MW have higher career and organizational commitment, report fewer days absent, and are characterized by a higher level of well-being. The aim of this study is to test a measure of MW, the Work and Meaning Inventory by Steger et al. This measure was created on theoretical background, and it constructs MW from three dimensions: psychological meaning, meaning-making, and greater good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…They are positive meaning, meaning-making through work, and greater good motivations. Subsequently, WAMI has been adapted across diverse cultural contexts, namely, Brazil (Leonardo et al, 2019), Israel (Steger et al, 2013), Italy (Di Fabio, 2018, Turkey (Akin et al, 2013), and Hungary (Csordás et al, 2022). The Turkish (Akin et al, 2013), Italian , and Hungarian (Csordás et al, 2022) versions have confirmed the original higherorder model.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They are positive meaning, meaning-making through work, and greater good motivations. Subsequently, WAMI has been adapted across diverse cultural contexts, namely, Brazil (Leonardo et al, 2019), Israel (Steger et al, 2013), Italy (Di Fabio, 2018, Turkey (Akin et al, 2013), and Hungary (Csordás et al, 2022). The Turkish (Akin et al, 2013), Italian , and Hungarian (Csordás et al, 2022) versions have confirmed the original higherorder model.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, WAMI has been adapted across diverse cultural contexts, namely, Brazil (Leonardo et al, 2019), Israel (Steger et al, 2013), Italy (Di Fabio, 2018, Turkey (Akin et al, 2013), and Hungary (Csordás et al, 2022). The Turkish (Akin et al, 2013), Italian , and Hungarian (Csordás et al, 2022) versions have confirmed the original higherorder model. The Brazilian (Leonardo et al, 2019) and Israeli (Steger et al, 2013) adaptations show a good fit for a one-dimensional model.…”
Section: Introductionmentioning
confidence: 97%
“…Yet on the contrary wider research confirmed Graeber's theories as shown in Figure 2 (Csordás et al 2022). Such fluctuation in results across different countries and fields inspired the authors to conduct similar studies on the Egyptian market of Engineering, Procurement, and Construction.…”
Section: Open Accessmentioning
confidence: 68%
“…However, recent researchers argue the validity of the mentioned theory (Soffia, Wood, and Burchell 2022), accordingly in 2022, Csordás et al (Csordás et al 2022) performed a test based on Work and Meaning Inventory (WAMI) (Snyder 2016), which showed that 64% of people had meaningful jobs (Figure 3). The results are relatively positive compared to Graeber's assumption (David Graeber 2018) yet negative compared to Duarte's WAMI results (Duarte-Lores et al 2023), which indicates that awareness of the employees and their connection to their output increased over the past period in Europe, however, furthermore efforts need to take place to enhance their engagement with different stakeholders, reinforcing the ownership towards the outputs of daily tasks.…”
Section: Open Accessmentioning
confidence: 99%
“…Ilyen elvek például az univerzalizmus (a természet és az emberek jóllétével való törődés), valamint a jóakarat (moralitás és érzelmi melegség) megélése (Plagnol & Hupper, 2010). Végül, az önkéntességből eredő egyik legerősebb intrinzik jutalom az az érzés, hogy másokon segíthetünk, ami a személyes kiteljesedés és elégedettség érzéséhez vezethet (Stukas, Snyder, & Clary, 2016), valamint az élet és a munka értelmesnek megélése, hiszen mások segítése által hozzájárulhatunk a nagyobb jóhoz is (Csordás, Matuszka, Sallay, & Martos, 2022;Steger, Dik & Duffy, 2012).…”
Section: A Motiváció éS a Szubjektív Jóllét öSszefüggései öNkénteseknélunclassified